50.2k views
1 vote
Use substitution to write an equivalent quadratic equation. (3x + 2)2 + 7(3x + 2) – 8 = 0

User Flimm
by
5.2k points

2 Answers

2 votes

Answer:

(u)^{2}+7(u)-8=0

Explanation:

User Minglyu
by
4.9k points
3 votes

Answer:

The equivalent quadratic equation corresponding to (3x + 2)² + 7(3x + 2) – 8 = 0 is y² + 7y – 8 = 0

Explanation:

Here given (3x + 2)² + 7(3x + 2) – 8 = 0

Substitute 3x + 2 as y

Solving

y² + 7y – 8 = 0

The equivalent quadratic equation corresponding to (3x + 2)² + 7(3x + 2) – 8 = 0 is y² + 7y – 8 = 0

User Cetnar
by
5.1k points